2000
DOI: 10.1007/s002470000346
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent myelinoclastic diffuse sclerosis: a case report of a child with Schilder's variant of multiple sclerosis

Abstract: Myelinoclastic diffuse sclerosis (MDS, Schilder's disease) is a rare CNS demyelinating disorder affecting mainly children and usually presenting as an intracranial mass lesion. We report the first case of recurrent intracranial MDS where the third episode of demyelination involved the cervical spinal cord. This may represent a subset of the disease, which should be considered as Schilder's variant (childhood form) of multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…reported that only 14% of patients had a monophasic course, and 70% of patients eventually developed definite multiple sclerosis . The first case of relapse of ‘tumefactive’ lesions was reported in a 6‐year‐old boy by Fitzgerald and Coleman . In the current study, 17 patients had a relapsing‐remitting course with recurrence of ‘tumefactive’ lesions rather than small discrete plaque‐like lesions characteristic of multiple sclerosis, with a median time to relapse of 4 months.…”
Section: Discussionsupporting
confidence: 45%
“…reported that only 14% of patients had a monophasic course, and 70% of patients eventually developed definite multiple sclerosis . The first case of relapse of ‘tumefactive’ lesions was reported in a 6‐year‐old boy by Fitzgerald and Coleman . In the current study, 17 patients had a relapsing‐remitting course with recurrence of ‘tumefactive’ lesions rather than small discrete plaque‐like lesions characteristic of multiple sclerosis, with a median time to relapse of 4 months.…”
Section: Discussionsupporting
confidence: 45%
“…It represents a more acute form of multiple sclerosis and is a very rare disease that occurs especially in children of both sexes. 7,11 The histologic features of brain tissue are identical to those of multiple sclerosis. The most common manifestation is an acute hemiplegia with headache, vomiting, and behavioral deterioration.…”
Section: Discussionmentioning
confidence: 93%
“…Several areas of variable size appear in the cerebellum, brain stem, and central white matter, especially in the periventricular region. [7][8][9] The case presented here fulfilled the diagnostic criteria of multiple sclerosis, but the appearance of lesions on MRI was atypical for multiple sclerosis, with large symmetric hyperintensities extending to the subcortical area that mimic those of Schilder's disease. 10 Schilder's disease is considered to be closely related to multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some children have a relentless progressive course, culminating in death. Other children may have remissions and exacerbations, with each subsequent exacerbation more severe and each remission less complete than previous episodes, until death supervenes [59, 60]. Schilder's disease is uniformly fatal [60, 61].…”
Section: Schilder’s Diseasementioning
confidence: 99%